Comparison of the utility of the Pentax Airway Scope (AWS) with that of the conventional Macintosh laryngoscope during chest compression: is the AWS an easy‐to‐use device for a novice?. Issue 3 (23rd April 2014) - Kotera, Atsushi; Irie, Hiroki; Iwashita, Shinsuke; Taniguchi, Junichi; Kasaoka, Shunji; Kinoshita, Yoshihiro
<x xml:space="preserve">Abstract</x> Aim The Pentax Airway Scope occasionally contacts the arm of the chest compressor at insertion because of its large body. Here, we test the Airway Scope's ease of use compared to that of the conventional Macintosh laryngoscope during chest compression, when operated by a novice. Methods We recruited 73 participants into this simulation study. Each participant carried out tracheal intubation using the two devices without and with chest compression. We recorded the time to intubation and the success rate. All of the participants completed a brief questionnaire after finishing the attempts. Results Data are medians and ranges. The time to intubation (seconds) without and with chest compression were 11 (7–57) and 13 (7–90) by the Macintosh laryngoscope, respectively, and 14 (6–46) and 15 (6–69) by the Airway Scope, respectively. The difference in the time to intubation between the groups without and with chest compression was significant for the Macintosh laryngoscope (P = 0.0434) but not significant for the Airway Scope. The time to intubation in the Airway Scope attempts were slightly longer than those in the Macintosh laryngoscope attempts (not significant). The success rate using the Macintosh laryngoscope with chest compression was significantly lower than that without chest compression (92% versus 100%, P = 0.0124). The success rate using the Airway Scope was 100%, but an accident occurred in four attempts. The questionnaire revealed that 54 participants preferred the Airway Scope and 19 preferred the Macintosh laryngoscope. Conclusion The Pentax Airway Scope appears to be better than the Macintosh laryngoscope during chest compression if the operator is a novice. However, using the Airway Scope does not always reduce the time to intubation.